1977
DOI: 10.1159/000152873
|View full text |Cite
|
Sign up to set email alerts
|

A Population Genetic Study of the Kota in the Nilgiri Hills, South India

Abstract: A population genetic study among the Kota of the Nilgiri Hills, South India, involved tests for abnormal haemoglobins, 5 red cell antigen systems, 4 serum protein and 13 red cell enzyme systems. Twelve systems are invariant in the Kota. The most distinctive characteristics are extremely low frequency of the A1gene and complete absence of A2in the ABO system, r(cde) in the Rh system, LDHCal-1among the enzyme systems as well as absence of abnormal haemoglobins. A comparison of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Similar frequencies of the acid-phosphatase alleles have been reported in the Bhils of Madhya Pradesh, tribals of Andhra Pradesh, and the Kurumba of Nilgiris (Papiha et al, 1978;Saha et al, 1976;Rao et al, 1978). A higher frequency o f p a has been reported in the Chenchu tribe of Andhra Pradesh (0.38) and the Kotas of the Nilgiris (0.46) by Ramesh et al (1980) and Ghosh et al (1977), respectively. The Kadar, I d a , and Toda of the Nilgiris and Yanadi tribe of Andhra Pradesh have a lower frequency ofpa (Saha et al, 1974(Saha et al, ,1976Reddy et al, 1982).…”
Section: Haemoglobin and G6pdsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar frequencies of the acid-phosphatase alleles have been reported in the Bhils of Madhya Pradesh, tribals of Andhra Pradesh, and the Kurumba of Nilgiris (Papiha et al, 1978;Saha et al, 1976;Rao et al, 1978). A higher frequency o f p a has been reported in the Chenchu tribe of Andhra Pradesh (0.38) and the Kotas of the Nilgiris (0.46) by Ramesh et al (1980) and Ghosh et al (1977), respectively. The Kadar, I d a , and Toda of the Nilgiris and Yanadi tribe of Andhra Pradesh have a lower frequency ofpa (Saha et al, 1974(Saha et al, ,1976Reddy et al, 1982).…”
Section: Haemoglobin and G6pdsupporting
confidence: 71%
“…The mongoloid populations have been reported to have a lower frequency of EsD1 compared to various Indian populations (Papiha and Nahar, 1977). The Bhils of Madhya Pradesh and Koya Doras of Andhra (Papiha et al, 1978, Veerraju et al, 1982 and the Kotas of the Nilgiris have a slightly higher frequency of EsDl (0.71-0.74; Ghosh et al, 1977).…”
Section: Haemoglobin and G6pdmentioning
confidence: 98%
“…It is apparent that the value of EsD2 is higher in South Indian than in North Indian populations (except for Kola and Harijans of Tamil Nadu) [Ghosh et al, 1977], Most of the Mongoloid populations are also showing high EsD-fre quencies. It is interesting to note that the EsD2 frequency of the Yanadi comes closer to the Mongoloid populations.…”
Section: Resultsmentioning
confidence: 90%
“…In a few other studies from A.P., the ACP A gene has been found to range between 0.16 and 0.20 [Busi et al, 1979;Ramesh et al, 1979;Blake et al, 1981] except in the Chenchu tribe, where it was found to be 0.459 [Ramesh et al, 1980]. Other studies from South India have revealed a high ACP A gene fre quency (0.467) in Kota [Ghosh et al, 1977] and in Thevars (0.361) of Tamil Nadu [Ananthakrishnan and Kirk, 1969], where as it was very low (0.107) in Kadars of Kerala [Saha et al, 1974], The frequencies obtained for the acid phosphatase genes in the A.P. populations do not show any var iation to suggest a clineal pattern in the distribution.…”
Section: Resultsmentioning
confidence: 94%